Design and Development Website of Research Institute, Case Study: Universitas Negeri Makassar - Ahmar, Ansari Saleh; Rusli, Rusli; Ihsan, Nasrul (Faculty of Communications Science, Dr. Soetomo University, 2017)
Abstract: The aim of this paper was to develop a website of research institue at Universitas Negeri Makassar, that can be accessed by many people to check information about reseach anytime and anywhere without the limit of time and location so that the disclosure of information research can be done. The method used in this research is the Software Development Life Cycle method with the three stages namely Initiation Phase, Development/Acquisition Phase, and Implementation Phase. The development of this information system using PHP and CodeIgniter as a its framework. This system development using PHP programming language and CodeIgniter Framework with MySQL database. Abstrak: Tujuan dari tulisan ini adalah dikembangkannya suatu Website Lembaga Penelitian di Universitas Negeri Makassar yang dapat diakses oleh berbagai pihak yang terkait dengan penelitian kapan saja dan dimana saja tanpa adanya batasan waktu dan lokasi sehingga keterbukaan informasi penelitian dapat terlaksana. Metode yang digunakan pada tulisan ini yaitu Metode Software Development Life Cycle dengan tiga tahapan yaitu fase awal, fase pengembangan, dan fase implementasi. Pengembangan sistem informasi ini menggunakan bahasa pemrograman PHP berbasis pada Framework CodeIgniter dengan basis data MySQL. Keywords: CodeIgniter, Information Systems, Website, Research Insitute, Universitas Negeri Makassar